A Control Optimization Model for Strengthening Corporate Governance through Digital Audit Technologies and Workflow Systems - Samson Oladele Dare; Joshua Oluwagbenga Ajayi; Onyeka Kelvin Chima (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
In an increasingly digital and compliance-driven business environment, traditional corporate governance structures often lack the responsiveness and transparency needed to mitigate emerging risks and regulatory pressures. This paper proposes a Control Optimization Model (COM) designed to strengthen corporate governance by integrating digital audit technologies and workflow automation systems. The model focuses on enhancing real-time visibility, accountability, and control efficiency across corporate operations by embedding automated checks, predictive analytics, and traceable workflows into governance processes. The COM is built on three interconnected pillars: intelligent audit trails, continuous control monitoring (CCM), and digitally enabled governance workflows. By leveraging technologies such as robotic process automation (RPA), artificial intelligence (AI), blockchain-based ledgers, and cloud audit platforms, the model allows organizations to transition from periodic manual audits to continuous, real-time governance assurance. It also facilitates risk-based prioritization, early anomaly detection, and data-driven decision-making by board members and senior management. Empirical insights from financial services, manufacturing, and logistics firms in emerging and developed markets reveal that the implementation of digital audit technologies improves internal control systems, reduces compliance costs, and enhances stakeholder confidence. However, integration challenges such as data silos, employee resistance, and skill gaps persist. The proposed model addresses these through a structured adoption roadmap, including digital readiness assessment, phased deployment, training, and continuous performance evaluation. This research contributes a practical governance innovation for organizations aiming to navigate the complexities of modern compliance environments. It enables alignment with international frameworks such as COSO, COBIT, and ISO 37000, while tailoring controls to organizational context. The COM is particularly valuable for large, multilayered institutions seeking to embed ethical conduct, financial integrity, and regulatory accountability into their operational DNA.